THE MEANING OF FRIENDSHIP: THE STORY OF A HUMAN AND DOG IN THE BUL ANIMATION - Gede Pasek Putra Adnyana Yasa (Yayasan Sinergi Widya Nusantara, 2022)
Purpose: Bul animation is full of meaning and moral messages. The meaning implied in it is the friendship between dogs and humans that occurs as a result of the gap in the social life of people in urban environments. The gap is interpreted through the interaction between the character of a scavenger and a dog. The purpose of this study is to analyze the interaction of the characters of a scavenger and a dog to form a story of friendship. Research methods: This study uses an interpretive qualitative semiotic analysis method. Findings: The research is centered on studying animation from the area of ??art studies, which specifically studies the meaning in every scene in the Bul animation. The meaning of friendship is created in the animated film Bul through a sign system in the form of icons, indexes, and symbols. The formation of the meaning of friendship can be observed in scenes 4 to scene 9. Friendship or friendship is a term that describes the behavior of cooperation and mutual support between two or more social entities. The meaning of friendship is created in a storyline and interaction between the characters in the animated film Bul, namely the scavengers and the dog. Through friendship, loyalty arises through the character of a dog who does not want to part with his friend (a scavenger). It signifies deep loyalty. Implication: The research results are helpful as a reference in creating animated works that can imply meaning or moral messages.